2011
DOI: 10.1111/j.1471-4159.2011.07266.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein D alters the early transcriptional response to oxidative stress in the adult cerebellum

Abstract: 1These authors contributed equally to this study.Abbreviations used: ApoD, Apolipoprotein D; FC, fold change; FDR, false discovery rate; GC, GeneChip; GO, gene ontology; hApoD, human ApoD; KO, knock-out; NS, nervous system; OS, oxidative stress; Pkcd, Protein kinase Cd; PQ, paraquat; RMA, robust multiarray average algorithm; RS, reactive species; Tg, transgenic; WT, wild-type. AbstractThe lipocalin Apolipoprotein D (ApoD), known to protect the nervous system against oxidative stress (OS) in model organisms, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 48 publications
(110 reference statements)
3
43
0
5
Order By: Relevance
“…7C). As it has been described for the vertebrate homologue ApoD in the mouse (Bajo-Graneras et al, 2011a, 2011bGanfornina et al, 2008;Ganfornina et al 2010), without additional stress the absence of NLaz might cause an imbalance in tissue homeostasis, generating a basal level of stress. This in turn might cause the observed slight GLaz up-regulation.…”
Section: Grasshopper Lazarillo Rescues Stress-sensitivity and Prematumentioning
confidence: 88%
“…7C). As it has been described for the vertebrate homologue ApoD in the mouse (Bajo-Graneras et al, 2011a, 2011bGanfornina et al, 2008;Ganfornina et al 2010), without additional stress the absence of NLaz might cause an imbalance in tissue homeostasis, generating a basal level of stress. This in turn might cause the observed slight GLaz up-regulation.…”
Section: Grasshopper Lazarillo Rescues Stress-sensitivity and Prematumentioning
confidence: 88%
“…Recently, we have found that acute high doses of PQ induce ApoD-dependent oligodendrocyte gene expression responses in the cerebellum (Bajo-Grañeras et al, 2011). In contrast, no genotype-dependent differential expression of myelin genes was seen in the SN in response to chronic PQ (not shown), indicating that this experimental paradigm is able to trigger a specific astroglial response to oxidative damage, with minor contribution of microglial or oligodendrocyte responses.…”
mentioning
confidence: 84%
“…9E). This up-regulation of GFAP protein could be controlled at transcriptional levels, since the lack of ApoD up-regulates Nf1a, a known activator of GFAP gene transcription, upon acute PQ treatment in the cerebellum (Bajo-Grañeras et al, 2011).…”
Section: Apod Modulates Astrocyte Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was associated with a role in regulating tissue homeostasis and in maintaining low levels of lipid peroxidation [13][14][15]. We have recently shown that ApoD contributes to reduce inflammation levels in ROS-injured tissues and promotes the clearance of lipid peroxides in cells [16,17].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%